New Terrain in Youth Development: The Promise of a Social Justice Approach - Ginwright, Shawn A. (Social justice, 2002)
Part of a special issue on pedagogies for social change. The writers present a youth-development model, demonstrating how external societal forces can have a substantial influence on the daily lives of urban youth. They suggest that a social justice framework is needed in order to account for the various forms of oppression and iniquities plaguing these youth and their communities. They believe that such a social justice model is needed to push the boundaries of the youth development field to be more intentional about the type of social world it seeks for its young people.